Nanotechnology: A New Strategy to Treat Dental Hypersensitivity - Rini Behera; Naomi Ranjan Singh; Satabdi Pattnaik; Siba Prasad Jena; Priyanka Paul Madhu; Vinitha Annavarjula (Institute of Medico-legal Publications Pvt Ltd, 2021)
Dental Hypersensitivity is the most commonly encountered dental problems associated with short, sharp painrising from exposed dentine in response to stimuli such as tactile, osmotic and chemical. Hypersensitivitymay present on several teeth, in one area of the mouth, or on one specific tooth. DHS should be differentiatedfrom another tooth sensitivity which may elicit from other clinical conditions such as dental caries,microleakage, cracked tooth or fractured restorations. Several treatment strategies such as desensitizationof nerve endings, masking of dentin tubules, occlusion of dentin tubules, and iontophoresis, are prevalentin clinical practices. Stannous ions, most commonly used in toothpastes as stannous fluoride, have beendemonstrated to occlude dentine tubules in vitro. SnF2 toothpaste formulations have been used for severaldecades and are widely accepted as an effective DH treatment. Recently advanced nanotechnology has takena wide leap in improving the various measures in the treatment of hypersensitivity by its nano particles.Nano structures have superior hardness, elasticity and flexural strength leading to its better application.Biomimetic particles desensitizing effect of nanocrystals which is caused by the progressive closure of thetubular openings of the dentine with plugs. These advancements have progressed the growth in the treatmentof Dental Hypersensitivity and have evoked a great amount of attention for improving disease prevention.